2013
DOI: 10.1136/annrheumdis-2012-201888
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of TNIP1 but not RHOB and PSORS1C1 as systemic sclerosis risk factors in a large independent replication study

Abstract: Introduction A recent genome-wide association study in European systemic sclerosis (SSc) patients identified three loci (PSORS1C1, TNIP1 and RHOB) as novel genetic risk factors for the disease. The aim of this study was to replicate the previously mentioned findings in a large multicentre independent SSc cohort of Caucasian ancestry. Methods 4389 SSc patients and 7611 healthy controls from different European countries and the USA were included in the study. Six single nucleotide polymorphisms (SNP): rs342070… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 25 publications
1
39
1
Order By: Relevance
“…TNIP1 regulates TNFAIP3 activity, thus it is also involved in the negative feedback regulation of the NF-kB signaling pathway. The association of this locus was reported for the first time in the GWAS by Allanore et al, and has been replicated in an independent study [17,49]. Interestingly, Allanore et al found a reduced expression of the gene in fibroblasts and affected skin samples from SSc patients [17].…”
Section: Non-hlamentioning
confidence: 72%
“…TNIP1 regulates TNFAIP3 activity, thus it is also involved in the negative feedback regulation of the NF-kB signaling pathway. The association of this locus was reported for the first time in the GWAS by Allanore et al, and has been replicated in an independent study [17,49]. Interestingly, Allanore et al found a reduced expression of the gene in fibroblasts and affected skin samples from SSc patients [17].…”
Section: Non-hlamentioning
confidence: 72%
“…41 A large followup study corroborated the association of TNIP1, but did not find any association with PSORS1C1 or RHOB. 42 Data from a followup of the French GWAS suggested that PPARG, which encodes peroxisome proliferatoractivated receptorγ, was asso ciated with SSc, although genomewide significance was not reached. 43 Another followup study found that IL12RB2, which encodes the β2 subunit of the IL12 receptor that is functionally linked to STAT4, CD247 and IFNγ, was associated with SSc.…”
Section: Gwas and Ssc Phenotypementioning
confidence: 99%
“…Over the past decade, genome‐wide association studies (GWAS) identified numerous NF‐κB susceptibility loci associated with autoimmune disease. Among these loci, TNIP1 polymorphisms have been strongly associated with psoriasis, psoriatic arthritis, SLE, and systemic sclerosis (SSc) (Figure ). Nair et al identified rs17728338 as a risk variant for psoriasis in patients of European ancestry .…”
Section: Tnip1 As a Disease Susceptibility Genementioning
confidence: 99%